Synthesis, Antimicrobial, and Anti-HIV1 Activity of Quinazoline-4(3H)-one Derivatives. (12th September 2013) - Vijayakumar, K.; Ahamed, A. Jafar; Thiruneelakandan, G.
Abstract : The present investigation aims to synthesize 11 compounds of quinazoline-1 derivatives and to test their antimicrobial and anti-HIV1 activities. A quick-witted method was developed for the synthesis of novel substituted quinazolinone derivatives by summarizing diverse diamines with benzoxazine reactions, and it demonstrated the benefits of typical reactions, handy operation, and outstanding product yields. These compounds were confirmed by elemental analysis, I R, 1 H NMR, 13 C NMR, and mass spectra. Then antimicrobial and anti-HIV1 activities of the compounds were tested in-vitro . It was found that compounds 7–11 possessed a wide range of anti microbial and anti-HIV1 activity.